Loyalty Programmes as Retailers’ Communication Tools during a Period of Social Change - Daniela Kollárová; Andrii Kushnarevych (Communication Today, 2025)
We are engaged in the study of loyalty systematically built and anchored in the form of consumer loyalty programmes. The aim of this theoretical review is to identify the problems and challenges retailers face in communicating with customers using loyalty programmes in a period of significant societal change. We examined 411 scholarly studies registered in the Web of Science database. Based on the results of the analysis, we identified the challenges faced by sponsoring organisations in the operation of modern loyalty programmes, which we divided into 14 categories by common features. The result is a compact theoretical overview about loyalty programmes. The aim of the empirical research, conducted through written inquiries and individual semi-structured interviews, is to find out how Generation Z respondents perceive loyalty programmes. The selected results reveal that there is a relatively large group of loyalty programme members who believe that they are not adequately rewarded by the sponsoring organisation.